Exploring the Mechanism Whereby Sinensetin Delays the Progression of Pulmonary Fibrosis Based on Network Pharmacology and Pulmonary Fibrosis Models - Xu, Yong; Hang, Wen-Lu; Zhou, Xian-Mei; Wu, Qi (Frontiers in Pharmacology, 2021)
The incidence of pulmonary fibrosis (PF), a progressively fatal disease, has increased in recent years. However, there are no effective medicines available. Previous results have shown that sinensetin probably has some curative effects on PF. Therefore, this paper aimed to predict the targets of sinensetin using a network pharmacology method and to confirm its effects and functional targets in PF using a mouse PF model. First, network pharmacology analysis showed that sinensetin has 105 functional targets, and 1698 gene targets closely relate to PF. The intersection of the functional targets and gene targets produced 52 targets for the treatment of PF with sinensetin. The PPIs led to several potential key target genes, including MAPK1, EGFR, SRC, and PTGS2. The results of GO and KEGG analysis suggested the crucial function of apoptosis in PF and its involvement in PI3K signaling pathway. Subsequently, we tested the molecular docking of sinensetin with the PI3K protein using the Autodock4 software. The results showed that sinensetin could fit well into several binding sites of the PI3K protein. Furthermore, we constructed a PF mouse model through one-off intratracheal instillation of bleomycin, and then intragastrically administered different concentrations of sinensetin to the model mice. Twenty-eight days later, the mice were sacrificed, and the lung tissues, serum, and bronchoalveolar lavage fluid (BALF) were collected. The in vivo tests showed that the body weight of model mice increased slightly compared with that of PF mice after intragastric sinensetin treatment. HE and Masson staining suggested a certain extent of reduction in the pathology of lung tissues. The expression of collagen I and III, as well as hydroxyproline in the lung tissues was reduced to a certain extent. IL-6 levels in the serum and BALF decreased markedly. The expression of vimentin and α-SMA in pulmonary tissues decreased. Cell apoptosis, as well as P-PI3K and P-AKT levels, in lung tissues also reduced. In summary, network pharmacology and in vivo test results suggest sinensetin as an effective treatment for PF, and the functional mechanism is likely related to PI3K-AKT signaling.